1995
DOI: 10.1074/jbc.270.4.1928
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Rlk, a Novel Protein Tyrosine Kinase with Predominant Expression in the T Cell Lineage

Abstract: The control of phosphorylation by protein tyrosine kinases represents an important regulatory mechanism in T cell growth, function, and differentiation. We have identified a 62-kDa murine protein tyrosine kinase predominantly expressed within the T cell lineage, which we have termed Rlk (for Resting lymphocyte kinase). rlk mRNA was found to be expressed in the fetal thymus as early as day 13 of embryonic development as well as in adult thymus and mature resting peripheral T cells. The sequence of rlk showed th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
62
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 39 publications
1
62
0
1
Order By: Relevance
“…The subsequent molecular cloning of four Tec-related kinases, Btk (2,3), Itk (also known as Emt or Tsk) (4-6), Bmx (7), and Txk (or Rlk) (8,9), revealed that these enzymes, together with Tec, constitute a distinct subfamily of nonreceptor PTKs. With the exception of Txk, the members of this subfamily possess a long NH 2 -terminal region consisting of a pleckstrin homology (PH) domain (10) and a Tec homology (TH) domain (11).…”
mentioning
confidence: 99%
“…The subsequent molecular cloning of four Tec-related kinases, Btk (2,3), Itk (also known as Emt or Tsk) (4-6), Bmx (7), and Txk (or Rlk) (8,9), revealed that these enzymes, together with Tec, constitute a distinct subfamily of nonreceptor PTKs. With the exception of Txk, the members of this subfamily possess a long NH 2 -terminal region consisting of a pleckstrin homology (PH) domain (10) and a Tec homology (TH) domain (11).…”
mentioning
confidence: 99%
“…Inducible T cell kinase (ITK) (1-5) belongs to the Tec family of nonreceptor protein tyrosine kinases, which includes Tec I and II (6,7), Bmx (8), Txk͞Rlk (9,10), and Bruton's tyrosine kinase (BTK) (11,12). ITK is expressed primarily in T cells (1-3, 5), with some expression detected in natural killer cells (4).…”
mentioning
confidence: 99%
“…More recently, several studies showed that various PH domains bind to phosphatidylinositol 4,5-bisphosphate (PIP 2 ) and inositol 1,4,5-trisphosphate (IP 3 ) through their positively charged residues in the amino-terminal four ␤-sheets (15,21,22). PIP 2 interactions with the amino-terminal PH domain of pleckstrin (21) and the PLC-␦1 PH domain (22) (30), and Txk/Rlk (31,32). In the present study we have characterized in detail the interaction between the Btk PH domain and PKC using an in vitro binding assay.…”
mentioning
confidence: 99%